Cuckoo about cuckoos: identification of Common and African cuckoos re-examined - Peacock, Faansie (Biodiversity Observations, 2014)
Birders who claim they can confidently identify any large grey cuckoo momentarily glimpsed are either deceiving themselves or deceiving their audience...The aim of this note is to re-assess the identification criteria aiding in the separation of Common and African Cuckoos, in a southern African context...